A humanized Gs-coupled DREADD for circuit and behavior modulation - Zhang, Qi; Wang, Ruiqi; Zhang, Liang; Li, Mengqi; Lin, Jianbang; Lu, Xiaoyang; Tian, Yixuan; Lin, Yunping; Liu, Taian; Chen, Yefei; Li, Yuantao; Cao, Jun; et al. (Frontiers in Cellular Neuroscience, 2025)
Designer receptors exclusively activated by designer drugs (DREADDs) play important roles in neuroscience research and show great promise for future clinical interventions in neurological diseases. The Gs-coupled DREADD, rM3Ds, modulates excitability in neuron subsets that are sensitive to downstream effectors of Gs protein. However, given the non-human nature of the rM3Ds backbone, risks about potential immunogenicity and tolerability exist when considering clinical translation. Here, we report the development of a whole sequence-humanized Gs-coupled DREADD, hM3Ds. We found that hM3Ds has a comparable DREADD ligand response profile to rM3Ds. We then selectively expressed hM3Ds in D1 medium spiny neurons (D1-MSNs) and found that hM3Ds was able to activate the D1-MSNs-mediated basal ganglia direct pathway and alleviate Parkinsonian phenotypes in a Parkinson’s disease mouse model. In conclusion, this engineered humanized Gs-coupled DREADD is suitable as an effective, and likely safer, DREADD tool for both research and future clinical applications.